Teknik Experiential Learning Meningkatkan Kemampuan Mengelola Emosi Pada Peserta Didik (FKIP, Universitas Palangka Raya, 2020)
The aims of this research was to find out how far the experiential learning method to help the students in emotional management related to anger and aggression behavior. The kind of this research was pre-experimental design with one-group pretest-posttest design. Purposive sampling was used to select the sample. The sample of this research was 7 students of MTs Muslimat NU Palangka Raya who had low emotional management ability. The instrument of this research was questionnaire of emotional management related to anger and aggression behavior. The technique of data analysis was used non parametric statistic with t-test two paired samples formula. The result of this research showed the students ability in emotional management related to anger and aggression behavior before received counseling group with experiential learning technique was 43% in low category, after received counseling group with experiential learning technique was 59% in the medium category. The difference of the level of emotional management ability related to anger and aggression behavior before and after received the counseling group with experiential learning technique was 16%. The result of t-test two paired samples formula was obtained t-test -8,725 and t table 1,943 it meant that Ha was accepted. The result showed that experiential learning technique was effective to improve the students’ ability in emotional management of the VIII grade students of MTs Muslimat NU Palangka Raya.